1997
DOI: 10.1017/s0031182096008724
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Giardia from a wild-caught sulphur-crested cockatoo (Cacatua galerita) established in vitro chronically infects mice

Abstract: An axenic culture of Giardia was established from a sample of infected intestine obtained following autopsy of a sulphur-crested cockatoo (Cacatua galerita). The cockatoo recently captured in the wild and with good muscle tone died along with several other cage mates, apparently of an overwhelming, acute infection of Giardia. Trophozoites which established in the traditional, axenic Giardia medium (TYI-S-33 with supplementary bile) were morphologically identical to G. duodenalis. When outbred Quackenbush Swiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…This strain was genetically similar to human isolates and was infective for mice, in which it established a chronic infection with high parasite burdens; the mice also lost up to 20% of their body weight, mimicking the human failureto-thrive syndrome (204,205). This is the first report of a bird isolate infecting mammals.…”
Section: Giardia Infectionmentioning
confidence: 86%
See 1 more Smart Citation
“…This strain was genetically similar to human isolates and was infective for mice, in which it established a chronic infection with high parasite burdens; the mice also lost up to 20% of their body weight, mimicking the human failureto-thrive syndrome (204,205). This is the first report of a bird isolate infecting mammals.…”
Section: Giardia Infectionmentioning
confidence: 86%
“…Such a benchmark example was recently described for a Giardia isolate which was found to be lethal for sulfur-crested cockatoos (204). This strain was genetically similar to human isolates and was infective for mice, in which it established a chronic infection with high parasite burdens; the mice also lost up to 20% of their body weight, mimicking the human failureto-thrive syndrome (204,205).…”
Section: Giardia Infectionmentioning
confidence: 93%
“…We have previously described an isolate of Giardia duodenalis (BRIS/95/HEPU/2041), referred to as 2041, established from a bird which died of an overwhelming infection with the parasite (31). Isolate 2041 chronically infects mice and produces higher peak parasite loads than the human Giardia isolate BRIS/83/HEPU/106 (referred to as 106) (31,32).…”
mentioning
confidence: 99%
“…Isolate 2041 chronically infects mice and produces higher peak parasite loads than the human Giardia isolate BRIS/83/HEPU/106 (referred to as 106) (31,32). Mice infected with 2041 suffer weight gain impairment, with the most severe weight deficit occurring at the time of maximum parasite load (32).…”
mentioning
confidence: 99%
“…5,7 In the wild, a wide variety of aquatic and semiaquatic mammals and birds 8 can be a source of waterborne Giardia cysts. 5,9,10 Studies on giardiasis in a variety of birds suggest they may be zoonotic reservoirs; 7,[9][10][11][12] however, these indications have not been proven. 13 As reviewed by Hopkins and others, 14 numerous studies demonstrated genetic and antigenic similarities among Giardia cyst isolates from humans and other mammalian hosts.…”
mentioning
confidence: 99%